Reclaiming energy from swine manure - Lipper, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Of several types of processes to capture energy from organic wastes, anaerobic digestion appears to be most attractive for swine wastes. It can stabilize the waste while producing bio-gas or methane gas. The concept has been extensively applied in Europe and India during energy shortages. Similar equipment has been used for gas production with domestic wastes. Anaerobic digestion has the additional attraction of preserving most of the plant nutrients for application to agricultural land. Primary disadvantages are the management required by sensitive digesters, the high initial investment required for equipment, and the fact that waste still must be disposed of after it is digested. Research is in progress to make the process more practical. Bacteriologists are investigating new strains of bacteria and culturing techniques. Engineers are investigating digester designs and operation to reduce construction and operational requirements and costs. Investments in such research appear more worthwhile with each rise in the cost of energy.
Swine Industry Day 1975 is known as Swine Day, 1975
Keywords: Swine; Energy; Maure